Eksplorasi Makna Job Satisfaction Gen Z Sebagai Karyawan Muda : Studi Kualitatif - Adinda Dinanti Revilina; Kiki Cahaya Setiawan (CV. Cendekiawan Muda Sriwijaya, 2025)
This research aims to how generation Z as young employees who have just entered the workforce understand the meaning of job satisfaction. The research method used is descriptive qualitative research method. The subject with the initials IY is 18 years old who has only worked for 9 months in a private company. The data collection method uses interviews and direct observation. The subject selection used purposive sampling with predetermined criteria. Job satisfaction or job satisfaction in each individual is certainly different. Job satisfaction is a feeling or emotional individual who is satisfied with his job. The results and discussion of subject IY are that the subject has satisfaction with his job even though he has hopes of getting a flexible job, but the subject has high satisfaction with his job. The subject views job satisfaction as a positive environment and supportive coworkers and superiors.